Communication for Seniors’ Inclusion in Today’s Society: The Effects of Digitisation on Active Ageing - Carmen Llorente-Barroso; Leopoldo Abad-Alcalá; Fausto Colombo (Media and Communication, 2023)
The progressive ageing of developed societies requires strategies and tools to ensure the well-being of older adults. The new communication paradigm offers ways to reduce the stigma associated with ageing and to improve the quality of life for older adults, but it can also create a dynamic that could put their inclusion at risk. The internet has fomented digital gaps that have exacerbated some of the exclusionary barriers faced by many older adults, while allowing a considerable number of others to maintain emotional ties with loved ones during the worst moments of the pandemic. This thematic issue addresses the different opportunities offered by Information and Communication Technology in improving the social inclusion and quality of life of seniors, but it also considers the risks that digitisation may pose by limiting certain rights of this group. Through the different articles in this issue, the repercussions of communication on the management of ageing are highlighted from different perspectives and methodological approaches. In this way, the complexity of the issue has been revealed, along with the need to address it from positive and constructive perspectives that reassess the role of older adults in the societies in which they live.